Vocational Lecturer Internship Program in Improving Front Office Teaching Competence at Polytechnic eLBajo Commodus - Dewi Sartika Umul; Gregorius A. Berybe; Yohanes Paulus Hanny Wadhi (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
Increasing human resources who are able to provide Front office services in accordance with needs, needs to be done by Politeknik eLBajo Commodus as a vocational college to improve the quality of education that can meet the needs of industry, especially hospitality industry. One of the mechanisms is to open internship opportunities for lecturers. The implementation of teaching activities certainly needs adjustment to changes that occur in the industrial world. This is based on tourism characteristics that often change along with the development of technology and knowledge. New trends and habits continue to emerge that require the world of vocational education to metamorphose according to the circumstances and needs of the industry. The method used in this study is a causative method using a self-direct learning approach, Problem-based learning, observation, interviews and literature studies during the internship process which was carried out for one month at Sudamala Komodo Resort. This study shows several adjustments related to the theory of teaching Front Office courses. These differences include the front office organizational structure and its duties and functions, the check-in process, registration form, comset rate, room assignment, bell boy, house bank, courtesy call, and check out tailored to the needs and circumstances of the hotel and environment at Sudamala Komodo Resort.